2004
DOI: 10.3201/eid1011.040516
|View full text |Cite
|
Sign up to set email alerts
|

Nucleocapsid Protein as Early Diagnostic Marker for SARS

Abstract: Serum samples from 317 patients with patients with severe acute respiratory syndrome (SARS) were tested for the nucleocapsid (N) protein of SARS-associated coronavirus, with sensitivities of 94% and 78% for the first 5 days and 6–10 days after onset, respectively. The specificity was 99.9%. N protein can be used as an early diagnostic maker for SARS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
137
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(145 citation statements)
references
References 9 publications
8
137
0
Order By: Relevance
“…The NP is involved in the pathological reaction to human coronavirus and is a key antigen for the development of a sensitive diagnostic assay He et al, 2005). Che et al (2004) reported that NP in the serum samples of SARS patients can be detected as early as 1 day after disease onset.…”
Section: Discussionmentioning
confidence: 99%
“…The NP is involved in the pathological reaction to human coronavirus and is a key antigen for the development of a sensitive diagnostic assay He et al, 2005). Che et al (2004) reported that NP in the serum samples of SARS patients can be detected as early as 1 day after disease onset.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid laboratory diagnosis mostly relied on nucleic acid amplification assays, using the SARS-CoV open reading frame 1b or nucleoprotein gene as targets in the detection of respiratory specimens, stool, urine, blood, and lung tissue Lau et al, 2005a;Poon et al, 2003;Poon et al, 2004;Poon et al, 2005b). Diagnosis rarely relied on enzyme immunoassay (EIA) for viral nucleocapsid protein antigen detection on patients' sera (Che et al, 2004a;Che et al, 2004b;Lau et al, 2004c). The nucleoprotein (NP) gene and protein were chosen as targets for RT-PCR and EIA because NP is the most abundantly expressed mRNA and protein in the infected cells, and should therefore give a higher sensitivity.…”
Section: Clinical Symptommentioning
confidence: 99%
“…Initially, clinical symptoms and epidemiologic linkage were diagnostics for SARS followed by serologic testing, viral culture and PCRbased methods (Wu et al, 2003;Yam et al, 2003). Now, reagents are also available for Nucleocapsid (N) protein and Spike (S) protein detection (Che et al, 2004;Sunwoo et al, 2012).…”
Section: Diagnosticsmentioning
confidence: 99%